Human Problem in The Views of Aziziddin Nasafi - Rasulov Ortiq (Peerian Journals Publishing, 2024)
In this article, Azizidin Nasafi's views on human are revealed based on the comprativistic analysis of knowledge in the field of sharia, tariqat (theology of Sufism), wisdom (philosophy). Also, is explained the philosophical basis of the idea of a perfect person in the teaching of Azizidin Nasafi
Keywords: Aziziddin Nasafi; a perfect person; philosophy; mysticism